Terror Risk Perception and Fear of Terror in Turkey: Predictors, Bases and Consequences - Gün Çınğı, Tuba (Terrorism and political violence, 2022)
This study was conducted in Ankara, Turkey, which has experienced a number of serious terrorist attacks in recent years. A mixed-methods research approach was used in this study and findings were based on 400 questionnaires and twenty in-depth interviews. This study tries to evaluate the risk perceptions of individuals, their fear of terror, and their associated reflections in daily life. It also attempts to determine the degree to which theories of fear of crime can explain risk perceptions and fear of terrorism. The results show that the perceived terror risk and the fear level are high. The Turkish case shows that theories of fear of crime fail to explain adequately the fear of terror.